Blue Light Induces Phosphorylation at Seryl Residues on a Pea (Pisum sativum L.) Plasma Membrane Protein. - Short, T. W. (1994)
We have partially characterized the blue-light-stimulated in vitro phosphorylation of a membrane protein from etiolated Pisum sativum L. stems. Properties of the response have implicated its involvement in signal transduction of phototropic stimuli (T.W. Short, W.R. Briggs [1990] Plant Physiol 92: 179-185; P. Reymond, T.W. Short, W.R. Briggs [1992] Proc Natl Acad Sci USA 89: 4718- 4721). Analysis of proteolysis products and phosphoamino acidanalysis indicate that the substrate protein is phosphorylated on multiple seryl residues. Kinetics of the in vitro reaction show phosphorylation to be complete within 2 to 5 min at 30[deg]C in either light-exposed or dark-control plasma membrane preparations, regardless of whether the membranes were first solubilized in Triton X-100. Nucleotide competition assays show the kinase to be ATP specific. The pH optimum covers a broad range with a maximum near 7.5. A wide array of salts inhibits the phosphorylation at high concentrations, but millimolar concentrations of Mg2+ are required to form Mg.ATP complexes for maximal activity, whereas excess free Mg2+ or Ca2+ are not required for the reaction.